Efeitos do treinamento resistido na síndrome metabólica: uma revisão sistemática com meta-análise e um ensaio clínico randomizado - Lemes, Ítalo Ribeiro [UNESP] (2015)
Background: Metabolic syndrome (MS) is the clustering of risk factors for cardiovascular diseases, such as hyperglycemia, dyslipidemia, increased waist circumference and hypertension. Regular physical activity is an important strategy for the treatment and prevention of metabolic and clinical changes to metabolic syndrome (MS). Resistance training (RT) is a low-cost method that can be used in the treatment and prevention of cardiovascular events. However this method has produced controversial results in relation to the risk factors of MS. Aim: To summarize the effects of resistance training on MS risk factors. Methods: The Medline, PEDro, EMBASE, SPORTDiscus and The Cochrane Library databases were searched from their earliest records to 10 January 2015. Only randomized controlled trials that compared resistance training with a control group were included in this review. The quality and data of the included studies were assessed by two independent reviewers...